Flow Injection With inhibited Chemiluminescence Method for the Determination of Adrenaline Hydrochloride - Yousif J. Azeez (مجلة جامعة الانبار للعلوم الصرفة, 2012)
A simple rapid and accurate flow injection inhibitory chemiluminescence method has been developed for the determination of adrenaline hydrochloride based on its inhibition of the chemiluminescence from the luminol ،V potassium hexacyanoferrate (III) system. The linear range of determination is 8.0 „e 10-12 ،V 8.0 „e 10-10 mgl-1 for adrenaline hydrochloride and the detection limit is 4.0 „e 10-9 g ml-1. The method has been applied to determine the content of adrenaline in pharmaceutical preparation with satisfactory results.